Effect of Intermediate Agents and Preheated Composites on Repair Bond Strength of Silorane-Based Composites - Fereshteh Shafiei; Sahar Akbarian; Marzieh Daryadar (Tehran University of Medical Sciences, 2016)
Objectives: Repairing composite restorations is a challenging procedure especially when two different types of composites are used. This study aimed to compare the repair strength of silorane-based composite (SC) (Filtek P90) with that of preheated SC, methacrylate composite (MC)(Z250), flowable MC (Filtek Supreme Plus) and different adhesive/composite combinations. Materials and Methods: Eighty-four SC specimens were fabricated and randomly divided into seven groups (G). In the control group (G7), SC was bonded immediately to SC. The other specimens were water-aged for two months and were then roughened, etched and repaired with the following materials: G1) Silorane Adhesive Bond (SAB)/SC; G2) Preheated SC; G3) SAB/MC; G4) Adper Single Bond (SB)/MC; G5) Flowable MC/MC; G6) Preheated MC. After water storage and thermocycling, the repaired specimens were subjected to shear bond strength testing. The data were analyzed using ANOVA and Tukey's test. Results: Preheated SC and MC, flowable MC and SAB/SC resulted in bond strength comparable to that of the control group. Preheated SC showed significantly higher bond strength when compared to SAB/MC (P=0.04) and SB/MC (P<0.001). Bond strength of SB/MC was significantly lower than that of the other groups (P<0.05), except for SAB/SC and SAB/MC. Conclusion: All repairing materials except for SB/MC resulted in bond strength values comparable to that of the control group. Repair with preheated SC yielded the highest bond strength.